When you're beyond information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Please share these proverbs in Spore:'A group can never become a community unless it develops the habit of deep, respectful listening to one another.' Sierra Leone 'To try and to fail is not laziness.' Sierra Leone 'When spider webs unite, they can...